POLITICAL LANDSCAPE DYNAMICS IN POST-DECADE YEMENI REVOLUTION: A LITERATURE REVIEW - Septyanto Galan Prakoso; Ferdian Ahya Al Putra; Edo Artima Kasla (CMES (Center of Middle Eastern Studies), 2023)
During the decade following the Arab Spring and the Yemeni Revolution, significant changes and dynamics occurred in Yemen, particularly in the realms of politics and security. The current situation can be categorized as "stable" due to the absence of escalating conflicts between the parties involved. However, the cessation of hostilities between the Houthi rebels and the Yemeni government, supported by a coalition of Arab countries, has the potential to create new challenges. Additionally, the ongoing humanitarian crisis resulting from the Yemeni conflict continues to require international attention. Despite considerable attention given to the current state of Yemen, there is a lack of scholarly research utilizing scientific literature to examine the condition of Yemen a decade after the revolution. Consequently, this article aims to review the Yemeni Revolution after ten years, using relevant publications from 2012 to 2022 obtained through Google Scholar and the Publish or Perish application. The data will be visualized using the Vosviewer application as a basis for analysis. The findings of this research reveal the complex conditions underlying the ten-year conflict that emerged in the aftermath of the Yemeni Revolution, characterized by multifaceted conflicts interrelated with various factors that have prolonged the crisis.